PENGARUH SISTEM PENGENDALIAN INTERNAL, WHISTLEBLOWING SYSTEM, MORALITAS, KEPUASAN KERJA, KOMPETENSI SUMBER DAYA MANUSIA,DAN KOMITMEN ORGANISASI TERHADAP PENCEGAHAN FRAUD - Cancera, Radita; Trisnawati, Rina (AKUNTANSI DEWANTARA, 2025)
The purpose of this study was to determine the effect of internal control systems, whistleblowing systems, morality, job satisfaction, human resource competency, and organizational commitment on fraud prevention in village fund management at the Village Head Offices in Kebakkramat District, Karanganyar Regency. This type of research uses quantitative research. The population in this study were all village apparatus or officials who worked in the village head's office located in Kebakkramat District, Karanganyar Regency, Central Java. The sampling technique used purposive sampling technique and obtained a sample of 80 respondents. Data collection techniques with questionnaires distributed to the research sample. Data analysis techniques used multiple linear regression analysis. The results showed that internal control systems, whistleblowing systems, job satisfaction, and organizational commitment had an effect on fraud prevention. While morality and human resource competency did not affect fraud prevention